Translational approach to heart failure - Vanderheyden, Marc; Bartunek, Jozef (Springer New York, 2013)
This book reviews multidisciplinary and translational state-of-the-art management of heart failure with emphasis on burning clinical questions and challenges faced by the heart team. The refined pathophysiologal understanding of the heart failure syndrome together with the surge of new technological advances led to innovative medical and interventional treatment strategies improving the outcome of heart failure patients. However the complex interplay between the clinical presentation and the array of the interventions requires a coordinated multidisciplinary "heart team" approach involving various specialists in the cardiovascular field including clinicians, interventionalists, surgeons and cardiac intensivists. In this book, opinion leaders will review of state-of-the-art management of heart failure with particular emphasis on burning clinical questions and challenges faced by the heart team. New medical and interventional therapies for chronic and acute heart failure are addressed by bridging bench to bedside translation in science and technology into practical clinical application and guidance.